Roasting method for controlling pore defect of quartz sand and improving stacking density

By using the alternating method of pre -heating and decarburizing and high -temperature sintering during the process of quartz sand roasting, the problem of low and low accumulation density of quartz sand gas pores was solved, and efficient carbon removal and powder contraction were achieved. The pores are high and have high accumulation density, and have good industrial application prospects.

CN119370854APending Publication Date: 2025-01-28CHANGFEI QUARTZ TECH (WUHAN) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411508782.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the pore defects of quartz sand and improve its bulk density, resulting in excessive pores and low bulk density of quartz sand after calcination.

Method used

A baking method includes a pre -heating and dehydration stage and a high temperature sintering stage. First of all, the vacuum environment and oxygen -containing atmosphere environment is alternately processed to achieve fully removal of carbon; then at high temperature, the vacuum and inert gas are treated alternately to promote the full contraction and sintering of the powder.

Benefits of technology

Through the roasting method, the obtained quartz sand has no obvious pores, the accumulation density is ≥1.3g/cm3, and it is more energy -saving than the traditional baking method, and has a good industrialization prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370854A_ABST
    Figure CN119370854A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of quartz sand, and discloses a roasting method for controlling the pore defect of quartz sand and increasing the stacking density, which comprises the following steps: 1) drying silicon dioxide gel prepared by a sol-gel method to obtain silicon dioxide powder; (2) the silicon dioxide particles are placed in a roasting furnace, the furnace temperature is preheated to 400-700 DEG C after vacuumizing is conducted, then the furnace is maintained in a vacuum environment for a period of time, then oxygen-containing atmosphere is filled into the furnace and maintained for a period of time, the vacuum environment and the oxygen-containing atmosphere environment are alternately conducted, and sufficient decarburization is achieved; and (3) vacuumizing again, raising the furnace temperature to 1100-1300 DEG C, maintaining for a period of time in a vacuum environment, filling inert gas into the furnace, maintaining for a period of time, alternately vacuumizing and filling the inert gas, and sintering the quartz sand. According to the method, preheating is performed for sufficient decarburization, then high-temperature sintering is performed, the finally obtained quartz sand does not have obvious air holes, and the bulk density is larger than or equal to 1.3 g / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz sand, and particularly relates to a roasting method for controlling quartz sand pore defects and improving packing density. Background Art

[0002] High-purity quartz sand generally refers to products with a silicon dioxide (SiO2) content of more than 99.95%. High-purity quartz sand is widely used, covering many fields from daily life to high-tech industries. Generally speaking, the acquisition of high-purity quartz sand mostly depends on the purification of natural quartz sand. The quality of the quartz sand mine itself has a great influence on the purity of quartz sand. For example, the American Unimin Company relies on high-quality quartz sand mines such as Spruce Pine and Ottawa to form a product monopoly in the global high-end quartz sand market.

[0003] Another way to obtain high-purity quartz sand is chemical synthesis. Compared with the purification of natural quartz sand, chemically synthesized quartz sand is not restricted by geographical location and has a controllable route. The reaction can be doped and treated based on product needs, which can achieve many advantages such as customization and scale. my country started late in understanding chemically synthesized quartz sand. After years of development, it has basically achieved self-sufficiency in the mid- and low-end markets, but it still has a big gap with foreign countries in the high-end quartz sand market. Existing research on quartz sand mainly focuses on solving the purity problem of quartz sand. There is still a lack of further research on deeper issues related to quartz sand, such as controlling quartz sand pore defects and improving packing density. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a calcination method for controlling pore defects of quartz sand and improving bulk density in view of the shortcomings of the prior art. The calcination method includes a preheating decarburization stage and a high-temperature sintering stage. The quartz sand finally obtained has no obvious pores and a bulk density of ≥1.3g / cm 3 .

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a calcining method for controlling pore defects of quartz sand and improving the packing density, comprising the following steps:

[0006] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder;

[0007] 2) Place the silicon dioxide particles in a calcining furnace, preheat the furnace to 400-700°C after evacuating the furnace, and then maintain the furnace in a vacuum environment for a period of time, then fill the furnace with an oxygen-containing atmosphere and maintain the furnace for a period of time, alternate between the vacuum environment and the oxygen-containing atmosphere to achieve full decarburization;

[0008] 3) After vacuuming again, the furnace temperature is raised to 1100-1300°C, and then maintained in a vacuum environment for a period of time, and then inert gas is filled into the furnace and maintained for a period of time, and vacuuming and filling with inert gas are performed alternately to sinter the quartz sand.

[0009] In the above scheme, the sol-gel method is to prepare silica gel by hydrolyzing oxysilanes such as tetramethoxysilane and tetraethoxysilane.

[0010] In the above solution, the particle size of the silicon dioxide powder is 50-1000 μm.

[0011] In the above scheme, in step 2), the heating rate of the furnace temperature is 200-500°C / h.

[0012] In the above scheme, in step 2), the vacuum degree of the vacuum environment is 0.01-10Pa.

[0013] In the above scheme, the volume fraction of oxygen in the oxygen-containing atmosphere is 20-80%, and the rest is inert gas.

[0014] Furthermore, the inert gas in the oxygen-containing atmosphere is one or more of Ar, He, and N2.

[0015] In the above scheme, the volume fraction of oxygen in the oxygen-containing atmosphere is gradually increased during the alternating cycle.

[0016] In the above scheme, the oxygen-containing atmosphere is introduced for 1-10 minutes.

[0017] In the above scheme, the pressure of the oxygen-containing atmosphere is 0.1-0.5 MPa.

[0018] In the above scheme, in step 2), the vacuum environment is maintained for 0.5-4 hours at a time, and the oxygen-containing atmosphere is maintained for 0.5-4 hours at a time, and the alternating cycles are repeated for 2-10 times.

[0019] In the above scheme, in step 3), the heating rate of the furnace temperature is 100-400°C / h.

[0020] In the above scheme, in step 3), the vacuum degree after evacuation is 0.01-50Pa.

[0021] In the above scheme, in step 3), the inert gas is one or two of He and N2.

[0022] In the above scheme, in step 3), the inert gas introduction rate is 2-10 L / min.

[0023] In the above scheme, in step 3), the pressure after filling with inert gas is 0.1-0.7 MPa.

[0024] In the above scheme, in step 3), the maintenance time after vacuuming is 2-12 hours at a time, and the maintenance time after filling with inert gas is 2-12 hours at a time, and the alternating cycles are 2-12 cycles.

[0025] In the above scheme, the quartz sand has no obvious pores, a bulk density of ≥1.3g / cm3, and a hydroxyl content of ≤30ppm.

[0026] The main technical concepts of the present invention are as follows:

[0027] The sol-gel method is a conventional method for synthesizing quartz sand. Although some alcohol can be removed during the heating process of the sol, a certain amount of alcohol and siloxane will remain. These organic "impurities" will appear in the form of carbon during high-temperature calcination. In general, the traditional calcination method directly and quickly heats up to above 1100°C for sintering. Although this can remove carbon, the carbon dioxide generated by adhering to the quartz sand will diffuse too fast due to the high temperature. At high temperatures, the interior of the quartz sand will become more compact, making it easy for carbon dioxide to form pores during rapid diffusion, affecting the packing density of the quartz sand. Therefore, during the calcination process, the carbon needs to be completely removed before the calcination temperature is raised to obtain quartz sand with fewer pores.

[0028] The applicant has found that residual carbon begins to produce CO2 at 400°C, and the rate of producing the corresponding gas increases with the increase in evaporation temperature. This is because O2 undergoes chemical adsorption on the carbon surface and is converted into adsorbed C=O, and then further forms CO2 and leaves the surface. Since chemical adsorption requires activation energy, an increase in temperature will lead to enhanced chemical adsorption of O2, thereby increasing the rate of chemical reaction. However, when the chemical adsorption reaches the maximum value, raising the temperature again will cause the adsorption capacity of O2 to weaken. Therefore, it is preheated to 400-700°C, and the vacuum environment and oxygen-containing atmosphere environment are used alternately. In the vacuum environment, the concentration gradient is used to exhaust the gas in the silica powder (such as oxygen, nitrogen or residual alkane gas in the air) as much as possible. At the same time, according to the Maxwell-Boltzmann distribution, using the mean free path and average velocity of molecules in an ideal gas, it can be inferred that the gas diffusion coefficient follows the following relationship with temperature and pressure: the higher the temperature and the thinner the gas, the faster the diffusion rate. Therefore, although a high concentration of oxygen atmosphere can increase the decarburization rate, it is not conducive to the full diffusion of oxygen into the interior of the quartz sand. Therefore, the use of an oxygen concentration gradient atmosphere can allow O2 to fully diffuse into the powder and react quickly with carbon to fully remove carbon. Then the temperature is raised to 1100-1300°C, and vacuuming and inert gas filling are alternately treated. Vacuuming can control the hydroxyl content. Vacuuming and inert gas filling sintering can promote the full shrinkage of the powder, making it dense and pore-free. The final quartz sand has no obvious pores, and the packing density can be increased and the hydroxyl content can be controlled.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention develops a new calcination method to solve the problem of excessive pores and low bulk density of quartz sand after calcination. The method comprises the following steps: firstly, preheating and decarburization are performed, during which a vacuum environment and an oxygen concentration gradient atmosphere are used alternately to fully remove carbon. Then, high-temperature sintering is performed, during which vacuuming and inert gas filling are used alternately to fully shrink and sinter the powder. The quartz sand finally obtained has no obvious pores and a bulk density of ≥1.3g / cm 3 , and is more energy-efficient than direct high-temperature treatment in traditional roasting methods. This roasting method has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM image of the quartz sand prepared in Example 1.

[0032] Figure 2 This is the SEM image of the quartz sand prepared in Comparative Example 2. DETAILED DESCRIPTION

[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0034] In the following examples, the silica gel used was prepared by a sol-gel method, and the specific steps are as follows:

[0035] 1) Add tetraethoxysilane and 7 times the equivalent of high-purity water into a vertical stirred tank with a jacket;

[0036] 2) Then, warm water at 50°C was introduced into the jacket, and the hydrolysis reaction was carried out for 1 hour at a stirring speed of 50 ppm to obtain a uniform milky white sol;

[0037] 3) After stopping stirring, the mixture was allowed to stand for 30 minutes, and then heated with a jacket at 150° C. to remove methanol and water until a white gel was obtained, and then naturally cooled and aged to obtain a silica gel.

[0038] In the following examples, the bulk density was determined in accordance with GB / T 21354-2008 “General method for determination of tap density of powder products”; the hydroxyl content was tested using a general liquid cell method.

[0039] Example 1

[0040] A calcination method for controlling quartz sand pore defects and improving bulk density comprises the following steps:

[0041] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder with a particle size range of 50 to 1000 μm;

[0042] 2) Put the silica particles into a quartz glass crucible, and then place them together in a roasting furnace. After evacuating to a vacuum degree of 5Pa, preheat the furnace temperature to 600°C at a rate of 500°C / h, and then maintain this vacuum environment for 0.5h. Then, fill the furnace with oxygen-containing atmosphere to a pressure of 0.3MPa within 1min and maintain it for 0.5h. In this way, the vacuum environment and oxygen-containing atmosphere environment are alternately carried out for a total of 3 cycles, but the last oxygen-containing atmosphere environment maintenance time is adjusted to 1.5h, so that the total time of this stage is 4h, and sufficient decarburization is achieved;

[0043] The volume fraction of oxygen in the oxygen-containing atmosphere used for the first time is 30%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the second time is 50%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the third time is 70%, and the rest is N2;

[0044] 3) After evacuating the furnace to a vacuum degree of 5Pa, the furnace temperature was raised to 1300°C at a rate of 100°C / h, and then maintained in this vacuum environment for 3 hours. He was then filled into the furnace at a rate of 5L / min to a pressure of 0.3MPa and maintained for 3 hours. The vacuuming and inert gas filling were repeated for 5 cycles, i.e., the total time for this stage was 30 hours, and the quartz sand was sintered.

[0045] Figure 1 The SEM image of the quartz sand prepared in this example shows that no obvious pores can be observed. After testing, the bulk density of the quartz sand prepared in this example is 1.36 g / cm 3 , the hydroxyl content is 20ppm.

[0046] Comparative Example 1

[0047] The roasting method of this comparative example comprises the following steps:

[0048] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder with a particle size range of 50 to 1000 μm;

[0049] 2) Put the silica particles into a quartz glass crucible, and then place them together in a roasting furnace. After evacuating to a vacuum degree of 5Pa, preheat the furnace temperature to 600°C at a rate of 500°C / h, and then maintain this vacuum environment for 0.5h. Then, fill the furnace with an oxygen-containing atmosphere within 1min to a pressure of 0.3MPa and maintain it for 0.5h. The volume fraction of oxygen in the oxygen-containing atmosphere is 70%, and the rest is N2. The vacuum environment and the oxygen-containing atmosphere are alternated for 4 cycles, that is, the total time of this stage is 4h, to achieve full decarburization;

[0050] 3) After evacuating the furnace to a vacuum degree of 5Pa, the furnace temperature was raised to 1300°C at a rate of 100°C / h, and then maintained in this vacuum environment for 3 hours. He was then filled into the furnace at a rate of 5L / min to a pressure of 0.3MPa and maintained for 3 hours. The vacuuming and inert gas filling were repeated for 5 cycles, i.e., the total time for this stage was 30 hours, and the quartz sand was sintered.

[0051] After testing, some of the quartz sand particles prepared in this comparative example still have pores, and the bulk density is 1.2g / cm 3 , the hydroxyl content is 100ppm.

[0052] Comparative Example 2

[0053] The roasting method of this comparative example comprises the following steps:

[0054] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder with a particle size range of 50 to 1000 μm;

[0055] 2) Put the silica particles into a quartz glass crucible and then place them together in a roasting furnace. After evacuating to a vacuum degree of 5Pa, heat the furnace temperature to 1300°C at a rate of 500°C / h, and then maintain this vacuum environment for 0.5h. Then, fill the furnace with an oxygen-containing atmosphere to a pressure of 0.3MPa within 1min and maintain it for 0.5h. The vacuum environment and the oxygen-containing atmosphere are alternately performed for 3 cycles; wherein, the volume fraction of oxygen in the oxygen-containing atmosphere used for the first time is 30%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the second time is 50%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the third time is 70%, and the rest is N2; finally, the oxygen-containing atmosphere with a volume fraction of 70% is maintained for 30h to complete the sintering.

[0056] Figure 2 The SEM image of the quartz sand prepared in this comparative example shows that some quartz sand particles still have honeycomb pores. After testing, the bulk density of the quartz sand prepared in this comparative example is 1.0 g / cm 3 , the hydroxyl content is 150ppm.

[0057] Comparative Example 3

[0058] The roasting method of this comparative example comprises the following steps:

[0059] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder with a particle size range of 50 to 1000 μm;

[0060] 2) Put the silica particles into a quartz glass crucible, and then place them together in a calcining furnace. After evacuating to a vacuum degree of 5 Pa, preheat the furnace temperature to 600°C at a rate of 500°C / h. After maintaining for 4 hours, increase the furnace temperature to 1300°C at a rate of 100°C / h and maintain for 30 hours to complete sintering.

[0061] After testing, the bulk density of the quartz sand prepared in this comparative example is 0.9 g / cm 3 , the hydroxyl content is 180ppm.

[0062] Example 2

[0063] A calcination method for controlling quartz sand pore defects and improving bulk density comprises the following steps:

[0064] 1) drying the silica gel prepared by the sol-gel method to obtain silica powder with a particle size range of 50 to 1000 μm;

[0065] 2) Put the silica particles into a quartz glass crucible, and then place them together in a roasting furnace. After evacuating to a vacuum degree of 10Pa, preheat the furnace temperature to 600°C at a rate of 300°C / h, and then maintain this vacuum environment for 1 hour. Then, fill the furnace with an oxygen-containing atmosphere to a pressure of 0.2MPa within 1 minute and maintain it for 1 hour. In this way, the vacuum environment and the oxygen-containing atmosphere environment are alternately carried out for a total of 3 cycles, but the last oxygen-containing atmosphere environment maintenance time is adjusted to 3 hours, so that the total time of this stage is 8 hours, so as to achieve full decarburization;

[0066] The volume fraction of oxygen in the oxygen-containing atmosphere used for the first time is 20%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the second time is 50%, and the rest is N2; the volume fraction of oxygen in the oxygen-containing atmosphere used for the third time is 75%, and the rest is N2;

[0067] 3) After evacuating the furnace to a vacuum degree of 10Pa again, the furnace temperature is raised to 1200℃ at a rate of 200℃ / h, and then maintained in this vacuum environment for 5h. Then, He is filled into the furnace at a rate of 10L / min to a pressure of 0.3MPa and maintained for 5h. The vacuuming and inert gas filling are repeated for 3 cycles, that is, the total time for this stage is 30h, and the quartz sand is sintered.

[0068] After testing, the quartz sand prepared in this example has no obvious pores and a bulk density of 1.30 g / cm 3 , the hydroxyl content is 15ppm.

Claims

1. A roasting method for controlling pore defects in quartz sand and increasing bulk density, characterized in that: The following steps are involved: 1) drying the silica gel prepared by the sol-gel method to obtain silica powder; 2) Place the silicon dioxide particles in a calcining furnace, preheat the furnace to 400-700°C after evacuating the furnace, and then maintain the furnace in a vacuum environment for a period of time, then fill the furnace with an oxygen-containing atmosphere and maintain the furnace for a period of time, alternate between the vacuum environment and the oxygen-containing atmosphere to achieve full decarburization; 3) After vacuuming again, the furnace temperature is raised to 1100-1300°C, and then maintained in a vacuum environment for a period of time, and then inert gas is filled into the furnace and maintained for a period of time, and vacuuming and filling with inert gas are performed alternately to sinter the quartz sand.

2. The roasting method for controlling quartz sand pore defects and improving bulk density according to claim 1, characterized in that: In step 2), the vacuum environment is maintained for 0.5-4 hours at a time, and the oxygen-containing atmosphere is maintained for 0.5-4 hours at a time, and the two cycles are repeated for 2-10 times.

3. The roasting method for controlling quartz sand pore defects and improving bulk density according to claim 1, characterized in that: In step 2), the vacuum degree of the vacuum environment is 0.01-10 Pa, the pressure of the oxygen-containing atmosphere environment is 0.1-0.5 MPa, and the oxygen-containing atmosphere is introduced for 1-10 min.

4. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: The volume fraction of oxygen in the oxygen-containing atmosphere is 20-80%, and the rest is inert gas; the volume fraction of oxygen in the oxygen-containing atmosphere is gradually increased during the alternating cycle process.

5. The roasting method for controlling quartz sand pore defects and improving bulk density according to claim 4, characterized in that: In step 2), the inert gas in the oxygen-containing atmosphere is one or more of Ar, He, and N2; in step 3), the inert gas is one or two of He and N2.

6. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: In step 3), the maintenance time after vacuuming is 2-12 hours at a time, and the maintenance time after filling with inert gas is 2-12 hours at a time, and the alternating cycle is 2-12 cycles.

7. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: In step 3), the vacuum degree after evacuation is 0.01-50Pa, the pressure after filling with inert gas is 0.1-0.7MPa, and the inert gas flow rate is 2-10L / min.

8. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: The heating rate of the furnace temperature in step 2) is 200-500°C / h, and the heating rate of the furnace temperature in step 3) is 100-400°C / h.

9. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: The sol-gel method prepares silica gel by hydrolyzing alkoxysilane; the particle size of the silica powder is 50-1000 μm.

10. The roasting method for controlling pore defects of quartz sand and improving bulk density according to claim 1, characterized in that: The quartz sand has no obvious pores and a bulk density of ≥1.3g / cm 3 , hydroxyl content ≤30ppm.

Citation Information

Cited By

  • Preparation method of deep ultraviolet quartz glass and deep ultraviolet quartz glass

    CN120887638A

  • Multi-parameter closed-loop control method, device and equipment for large-size powder rod sintering

    CN122710575A